Effect of body mass index on survival in patients with metastatic colorectal cancer receiving chemotherapy plus bevacizumab: a systematic review and meta-analysis - Lang, Xiaohui; Tong, Chengliang; Yu, Yang; Li, Huiyan (Frontiers in Nutrition, 2024)
Aim: This systematic review and meta-analysis was to evaluate the relationship between body mass index (BMI) and the clinical outcomes in patients with metastatic colorectal cancer (mCRC) undergoing treatment with bevacizumab plus chemotherapy.The search for relevant literature was conducted across PubMed, Embase, Cochrane Library, and Web of Science, with the final search date being October 4, 2023.We utilized the weighted mean differences (WMDs), risk ratios (RRs), or Hazard ratios (HRs) as the metric for effect sizes, which were accompanied by 95% confidence intervals (CIs).Results: A total of 9 studies were included for analysis. The results indicated that nonobese patients with mCRC undergoing treatment with bevacizumab experienced a reduced overall survival (OS) at the six-month compared to their obese counterparts (RR: 0.97, 95% CI: 0.94 to 1.00, P= 0.047). Furthermore, no significant differences in one-year, two-year, and five-year OS, as well as PFS and median OS, were observed between obese and non-obese mCRC patients undergoing treatment with bevacizumab plus chemotherapy.These findings suggest that obesity may play a role in the short-term OS of patients with mCRC undergoing bevacizumab treatment. The clinical implications of these findings underscore the importance of considering patients' BMI in the context of mCRC care. This study may also help guide personalized treatment strategies and further research into the interplay between obesity, treatment efficacy, and patient survival in mCRC. However, further investigation is warranted to substantiate the BMI on survival in patients with mCRC receiving bevacizumab 3 findings of this study.